TRIBOLOGICAL PROPERTIES OF AL2O3-ZrO2 COMPOSITE COATING BY LUBRICATION - Riyadh A. Al-Samarai; Haftirman Haftirman (SINERGI, 2021)
Tribological investigations had been carried out on the plasma coating (Al2O3+ ZrO2) below dry and moist abrasion stipulations according to ASTM G134. Commercial motor oil 20W40 was used as a lubricant. At a rotational speed of 200 rpm, all experiments were carried out with ordinary loads of 10, 15 and 20 Nm. Electron microscopy for scanning and AFM was used to study of the layer sprayed with paint. The outcomes of the SEM and AFM evaluation confirmed that abrasive wear is normally decided by abrasive wear in dry abrasive conditions. The lubrication and moisture check confirmed a major reduce in wear from 10 to 15 N below regular loading, and a corrosion fee larger than 15 N was once discovered below regular loading. No impact of lubrication on wear used to discovered at high loading. No impact of lubrication on wear used to be discovered at high loads. It was also cited that the plasma coating manner to improve wear resistance. The experimental statistics acquired in this study are tremendous engineering functions such as reducing equipment and internal combustion engines.